2002
DOI: 10.1002/cne.10308
|View full text |Cite
|
Sign up to set email alerts
|

Retinal characteristics of the ornate dragon lizard, Ctenophorus ornatus

Abstract: The retina of a diurnal insectivorous lizard, Ctenophorus ornatus (Agamidae) was investigated using microspectrophotometry and light and electron microscopy. A prominent broad yellow band was observed that extended across the mid-retina. The yellow coloration was found to originate from both oil droplets and diffuse pigmentation within cone inner segments. Microspectrophotometric analysis revealed yellow oil droplets with variable absorption of wavelengths below 520 nm and transparent oil droplets with no dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
72
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 57 publications
12
72
2
1
Order By: Relevance
“…Previous studies based on a single technique have sometimes yielded contradictory results. For example, in the ornate dragon lizard, Ctenophorus ornatus (Agamidae), results of a behavioural test suggested UV vision (LeBas and Marshall, 2000), but MSP measurements later indicated that this species lacks UVS photoreceptors and is therefore blind to UV wavelengths (Barbour et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies based on a single technique have sometimes yielded contradictory results. For example, in the ornate dragon lizard, Ctenophorus ornatus (Agamidae), results of a behavioural test suggested UV vision (LeBas and Marshall, 2000), but MSP measurements later indicated that this species lacks UVS photoreceptors and is therefore blind to UV wavelengths (Barbour et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that diurnal geckoes are foveated while nocturnal geckoes are not, the superficial fovea of crocodilians may represent a halfway point between the two that reflects their arrhythmic lifestyle (Röll, 2001;Barbour et al, 2002). Alternatively, the similar ratio of eye size and SRP described above for crocodile juveniles and nocturnal geckoes may suggest that the crocodilian fovea is vestigial.…”
Section: Specialised Distribution Of Retinal Ganglion Cells and Its Rmentioning
confidence: 99%
“…The very narrow and superficial fovea in the vertical centre of the streak implies less lateral displacement of retinal ganglion cells than what occurs in the fovea of diurnal lizards (Chievitz, 1889;Laurens and Detwiler, 1921;Röll, 2001;Barbour et al, 2002). Given the fact that diurnal geckoes are foveated while nocturnal geckoes are not, the superficial fovea of crocodilians may represent a halfway point between the two that reflects their arrhythmic lifestyle (Röll, 2001;Barbour et al, 2002).…”
Section: Specialised Distribution Of Retinal Ganglion Cells and Its Rmentioning
confidence: 99%
See 1 more Smart Citation
“…All Iguania thus far studied show the same basic pattern of retinal photoreceptors. All appear to have tetrachromatic colour vision based on four classes of cone pigments with similar peak absorption wavelengths (l max ) [7,8,27,28]. Among the Gekotta, both nocturnal and diurnal forms have only three classes of photoreceptors (referred to as rods in the nocturnal forms, and cones in the diurnal).…”
Section: Introductionmentioning
confidence: 99%